การเลือกเอกลักษณ์ท้องถิ่นสำหรับพัฒนาผลิตภัณฑ์ชุมชน: กรณีศึกษากลุ่มวิสาหกิจชุมชนบ้านห้วยชมพู / Local Identity Selection for Community Product Development: Case Study of Baan Huay Chompoo Community Enterprise - Kunasri, Kasem; Panmanee, Chanita; Singkharat, Sombat; Suthep, Supa; Suthep, Duangta (Journal of Community Development Research (Humanities and Social Sciences); Vol 10 No 4 (2560): October-December 2017, 2017)
กลุ่มวิสาหกิจชุมชนบ้านห้วยชมพูเป็นแหล่งพัฒนาอาชีพเสริมให้กับคนในชุมชน ปัจจุบันกลุ่มวิสาหกิจฯ มีจุดอ่อนด้านทักษะฝีมือและความคิดสร้างสรรค์ในการพัฒนาผลิตภัณฑ์รูปแบบใหม่ อีกทั้งการออกแบบผลิตภัณฑ์ไม่ได้สะท้อนถึงของเอกลักษณ์ท้องถิ่น ปัญหานี้อาจก่อให้เกิดผลกระทบต่อรายได้ของคนในชุมชนในระยะยาว ดังนั้น งานวิจัยนี้จึงมีวัตถุประสงค์เพื่อเลือกเอกลักษณ์ท้องถิ่นสำหรับพัฒนาผลิตภัณฑ์ชุมชน กลุ่มตัวอย่าง 18 ราย ถูกเลือกแบบเจาะจงจากสมาชิกกลุ่มวิสาหกิจฯ จำนวน 10 ราย คนในชุมชน จำนวน 5 ราย นักวิชาการ จำนวน 2 ราย และเจ้าหน้าที่เทศบาลตำบลแม่แตง จำนวน 1 ราย ใช้การวิจัยเชิงปฏิบัติการแบบมีส่วนร่วมและการวิเคราะห์ตามลำดับชั้นเป็นเครื่องมือในการวิเคราะห์ ผลการวิจัย พบว่า ช้างแม่ตะมานเป็นเอกลักษณ์ท้องถิ่นที่สำคัญเป็นลำดับที่หนึ่ง ซึ่งถูกใช้เป็นทางเลือกในการพัฒนาผลิตภัณฑ์ต้นแบบ และออกแบบตราสินค้า บรรจุภัณฑ์ รวมถึงป้ายประชาสัมพันธ์ที่นำไปใช้ทำกลยุทธ์ทางการตลาด นอกจากนี้ผลการวิจัยทำให้ได้แบบจำลองสำหรับนำไปส่งเสริมยังพื้นที่อื่นๆ เพื่อให้เกิดความยั่งยืนของอาชีพในชุมชน      Baan Huay Chompoo community enterprise is a source of secondary occupation development for people in the community. Nowadays, this enterprise has weaknesses in skills and creativity in developing new products, as well as product design does not reflect local identity. This problem may affect on long-term income of people in the community. Consequently, this research aims to select the local identity for community product development. The 18 samples are purposively selected from 10 members of Baan Huay Chompoo community enterprise, five people in the community, two academicians, and one officer of Maetang Subdistrict Municipality. The participatory action research (PAR) and the analytic hierarchy process (AHP) approaches are used as the tools for analyzing. The results show that Maetaman Elephant is the first important local identity that is used as the alternative in developing product prototypes, brand, packages and signboard for creating marketing strategies. Moreover, the research findings lead to the model for promoting in the other areas to sustain the occupations in the community.
Keywords: เอกลักษณ์ท้องถิ่น, การสร้างตราสินค้า, ผลิตภัณฑ์ต้นแบบ, กระบวนการวิเคราะห์ตามลำดับชั้น